Analisis Strategi Pengembangan Usaha Kerupuk Nasi Bunga Seroja di Kampung Lubuk Pasing, Kec. Bayang, Kab. Pesisir Selatan - Natasya Faradila; Rika Widianita (Lembaga Yasin AlSys, 2026)
MSME business development strategies have become a focus in various previous studies; however, research that specifically discusses the development of traditional food-based businesses with limited internal resources remains limited. This study aims to analyze the business development strategy of the Bunga Seroja Rice Cracker business in Lubuk Pasing Village, Bayang Subdistrict, Pesisir Selatan Regency. This study employed a qualitative approach with a field research design. The research informants consisted of the business owner, employees, and consumers selected through the purposive sampling technique. Data were collected through observation, interviews, and documentation and were then analyzed using interactive analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that the business development strategy is still carried out conventionally and has not been optimally integrated. In the production aspect, the business process still depends on traditional methods and weather conditions. In the marketing aspect, the distribution reach is still limited to the local market. In the business capital aspect, the deferred payment system causes slow capital turnover. Meanwhile, in the human resource aspect, the use of casual labor leads to instability in production and product quality. These findings contribute to the development of business strategy studies, particularly in the context of traditional food-based MSMEs. The conclusion of the study emphasizes that the integration of production, marketing, capital, and human resource aspects is needed to support business sustainability. The practical implication is that business actors and the government need to design more effective development strategies through strengthening production capacity, improving capital management, stabilizing the workforce, and expanding market access.